Dependence of subseasonal to seasonal precipitation prediction on atmospheric and land initial conditions in the Energy Exascale Earth System Model - Dongze Xu; Zhaoxia Pu; Shixuan Zhang; Jeffrey Anderson; L. Ruby Leung (Climate Dynamics, 2026)

Systematic evaluation of atmospheric forcing, surface datasets, and mesh effects on kilometer-scale land surface and river modeling - Lingcheng Li; Gautam Bisht; Donghui Xu; Dalei Hao; Chang Liao; Dongyu Feng; Zeli Tan; Hongyi Li; Mingjie Shi; Tian Zhou; L. Ruby Leung (Journal of Hydrology, 2026)

Multivariate environmental and trait-based controls of transpiration in the Central Amazon Rainforest - Yilin Fang; Cristina Santos da Silva; Adam Collins; Bruno O. Gimenez; Kolby Jardine; Robinson I. Negrón-Juárez; Regison Oliveira; Valdiek da Silva Menezes; Kurt Solander; Gustavo Spanner; Jeffrey M. Warren; Cynthia L. Wright; et al. (Agricultural and Forest Meteorology, 2026)

Improving the prediction of daily reservoir releases over the CONUS using conditioned LSTM - Hoang Tran; Tian Zhou; Zeli Tan; Yilin Fang; L. Ruby Leung (Journal of Hydrology, 2025)

Improved Simulation of East Asian Summer Monsoon in the High-resolution CESM1 and Its Causes - Yingshuo Xiang; Lu Dong; Fengfei Song; Lixin Wu; L. Ruby Leung; Shengpeng Wang; Enze Dong; Hong Wang (Advances in Atmospheric Sciences, 2025)

Projections of future climate for U.S. national assessments: past, present, future - Samantha Basile; Allison Crimmins; Fredric Lipschultz; Kenneth E. Kunkel; Kate Marvel; Adam Terando; Claudia Tebaldi; David Pierce; Wenying Su; L. Ruby Leung; Katharine Hayhoe (Climatic Change, 2025)

Seasonal delay of Sahelian rainfall driven by an east–west contrast in radiative forcing in idealized CESM experiments - Hongqiang Dong; Fengfei Song; Fukai Liu; Hai Wang; Lu Dong; L. Ruby Leung; Jian Lu (Climate Dynamics, 2024)

Exploring the food-energy-water nexus in coupled natural-human systems under climate change with a fully integrated agent-based modeling framework - Jiaorui Zhang; Y.C. Ethan Yang; Guta W. Abeshu; Hongyi Li; Fengwei Hung; Chung-Yi Lin; L. Ruby Leung (Journal of Hydrology, 2024)

Region and cloud regime dependence of parametric sensitivity in E3SM atmosphere model - Yun Qian; Zhun Guo; Vincent E. Larson; L. Ruby Leung; Wuyin Lin; Po-Lun Ma; Hui Wan; Hailong Wang; Heng Xiao; Shaocheng Xie; Ben Yang; Kai Zhang; et al. (Climate Dynamics, 2024)
The Department of Energy (DOE)’s Energy Exascale Earth System Model (E3SM), including its atmosphere model (EAM), has many relatively new features. In a previous study we conducted a systematic parametric sensitivity analysis for EAM based on short, perturbed parameter ensemble (PPE) simulations, mainly focusing on global mean climate features and metrics. While parameter values in global climate models are generally invariant in space and time, model response to parameters perturbation may vary by regions and climate regimes, which motivates the need to better understand the EAM model behaviors and physics at regional scale and process level. In this study, using the same set of PPE simulations and a similar sensitivity analysis framework, we identify parameters that cause largest sensitivities over different regions and compare model responses in fast atmospheric processes to the parameters across different cloud regimes for several important cloud-related fidelity metrics. We find that cloud forcing has opposite response to some parameters over mid-latitude vs. tropical land. We also analyze how the parametric sensitivity varies as stratocumulus transitions to shallow convection and to deep convection over ocean. Low cloud forcing and shortwave cloud forcing in the subtropical eastern Pacific are most sensitive to the parameters controlling the width of the probability density function (PDF) of the subgrid vertical velocity ( w’ ) ( gamma ) and the damping of the w’ skewness ( c8 ) near the coast but become more sensitive to the parameter affecting the damping of the w’ variance ( c1 ) further offshore. Detailed interpretation of the spatial dependence of parametric sensitivity is provided. We also investigate how the parametric sensitivity evolves with prediction duration. This study improves our process-level understanding of cloud physics and parameterization and provides insights for developing more advanced regime-aware parameterization schemes in global climate model.

A new method for predicting hurricane rapid intensification based on co-occurring environmental parameters - Anushka Narayanan; Karthik Balaguru; Wenwei Xu; L. Ruby Leung (Natural Hazards, 2024)
Tropical cyclones (TCs) that undergo Rapid Intensification (RI) can pose serious socioeconomic threats and can potentially result in major damaging impacts along coastal areas. Considering the complexity of various physical mechanisms that play a role in RI and its relatively low probability of occurrence, predicting RI remains a major operational challenge. In this study, we propose a simple deterministic binary classification model based on the co-occurrence of environmental parameters (MCE) to predict an RI event. More specifically, the model determines the possibility of RI based on a simple count of the number of environmental predictors deemed favorable and unfavorable. We compare our model results to logistic regression (LR) and decision tree (DT) models, well-trained using the same set of environmental predictors. Results reveal that at an RI threshold of 30 kt, the MCE exhibits a critical success index score of 0.233 which is 14% higher than DT and LR model performances. When tested at multiple RI thresholds, the MCE displays relatively higher skill scores across multiple metrics. By simultaneously evaluating the favorability of predictors, the MCE is able to comparatively reduce the number of false alarms predicted when certain predictors are unfavorable toward RI. Interpreting these model results to gain a physical understanding of how co-occurring environmental parameters can affect RI, we highlight future directions for using models based on the MCE approach to understand and predict TC RI as well as other meteorological extremes.

One-way coupling of E3SM with ADCIRC demonstrated on Hurricane Harvey - Benjamin Pachev; L. Ruby Leung; Tian Zhou; Clint Dawson (Natural Hazards, 2023)

Tropical cyclone strength, precipitation, and environment in variable resolution CAM-MPAS simulations over Western North Pacific - Yuan Liang; Ben Yang; Minghuai Wang; Yipeng Guo; Koichi Sakaguchi; L. Ruby Leung (Climate Dynamics, 2023)

Correction to: Urbanization Impact on Regional Climate and Extreme Weather: Current Understanding, Uncertainties, and Future Research Directions - Yun Qian; T. C. Chakraborty; Jianfeng Li; Dan Li; Cenlin He; Chandan Sarangi; Fei Chen; Xuchao Yang; L. Ruby Leung (Advances in Atmospheric Sciences, 2023)
The article “Urbanization Impact on Regional Climate and Extreme Weather: Current Understanding, Uncertainties, and Future Research Directions”, written by Yun QIAN, TC CHAKRABORTY, Jianfeng LI, Dan LI, Cenlin HE, Chandan SARANGI, Fei CHEN, Xuchao YANG, and L. Ruby LEUNG was originally published electronically on the publisher’s internet portal on 25 of January 2022 with open access. With the author(s)’ decision, the copyright of the article changed from © The Author(s) 2022 to © Battelle Memorial Institute [2022]. The original article has been corrected.

Urbanization Impact on Regional Climate and Extreme Weather: Current Understanding, Uncertainties, and Future Research Directions - Yun Qian; T. C. Chakraborty; Jianfeng Li; Dan Li; Cenlin He; Chandan Sarangi; Fei Chen; Xuchao Yang; L. Ruby Leung (Advances in Atmospheric Sciences, 2022)
Urban environments lie at the confluence of social, cultural, and economic activities and have unique biophysical characteristics due to continued infrastructure development that generally replaces natural landscapes with built-up structures. The vast majority of studies on urban perturbation of local weather and climate have been centered on the urban heat island (UHI) effect, referring to the higher temperature in cities compared to their natural surroundings. Besides the UHI effect and heat waves, urbanization also impacts atmospheric moisture, wind, boundary layer structure, cloud formation, dispersion of air pollutants, precipitation, and storms. In this review article, we first introduce the datasets and methods used in studying urban areas and their impacts through both observation and modeling and then summarize the scientific insights on the impact of urbanization on various aspects of regional climate and extreme weather based on more than 500 studies. We also highlight the major research gaps and challenges in our understanding of the impacts of urbanization and provide our perspective and recommendations for future research priorities and directions.

A substantial role of soil erosion in the land carbon sink and its future changes - Zeli Tan; L. Ruby Leung; Hong‐Yi Li; Teklu Tesfa; Qing Zhu; Maoyi Huang (Global Change Biology, 2020)
Realistic representation of land carbon sink in climate models is vital for predicting carbon climate feedbacks in a changing world. Although soil erosion that removes land organic carbon has increased substantially since the onset of agriculture, it is rarely included in the current generation of climate models. Using an Earth system model (ESM) with soil erosion represented, we estimated that on average soil erosion displaces 5% of newly fixed land organic carbon downslope annually in the continental United States. In the lower Mississippi river basin and the Cascades, the fraction can be as large as 40%. About 12% of the eroded organic carbon is eventually exported to inland waters, which is equal to 14% of the simulated net carbon gain by terrestrial ecosystems. By comparing the eroded organic carbon export to rivers with the particulate organic carbon export to oceans, we demonstrated that a large fraction of the carbon export to rivers could have been mineralized in inland waters. Importantly, with a direct comparison of eroded and exported soil organic carbon and land net carbon uptake, we found that ESMs that ignore soil erosion likely offset the erosional carbon loss by increasing heterotrophic respiration implicitly. But as soil erosion and heterotrophic respiration respond differently to a warming climate, this unrealistic compensation would lead to biased predictions of future land carbon sink.

Structural changes and variability of the ITCZ induced by radiation–cloud–convection–circulation interactions: inferences from the Goddard Multi-scale Modeling Framework (GMMF) experiments - William K. M. Lau; Kyu-Myong Kim; Jiun-Dar Chern; W. K. Tao; L. Ruby Leung (Climate Dynamics, 2020)
In this paper, we have investigated the impact of radiation–cloud–convection–circulation interaction (RC3I) on structural changes and variability of the Inter-tropical Convergence Zone (ITCZ) using the Goddard Multi-scale Modeling Framework, where cloud processes are super-parameterized, i.e., explicitly resolved with 2-D cloud resolving models embedded in each coarse grid of the host Goddard Earth Observing System-Version 5 global climate model. Experiments have been conducted under prescribed sea surface temperature conditions for 10 years (2007–2016), with and without cloud radiation feedback in the atmosphere, respectively. Diagnostic analyses separately for January and July show that RC3I leads to an enhanced and expanded Hadley Circulation characterized by (1) a quasi-uniform warming and moistening of the tropical atmosphere and a sharpening of the ITCZ with enhanced deep convection, more intense precipitation and higher clouds, (2) extended drying of the tropical marginal convective zones, and extratropical mid- to lower troposphere, and (3) a cooling of the polar regions, with increased baroclinicity and midlatitude storm track activities. Computations based on the zonal mean thermodynamic energy balance equation show that the radiative warming and cooling are strongly balanced by local adiabatic processes associated with changes in large-scale vertical motions, as well as horizontal atmospheric heat transport. In the tropics, enhanced short-wave absorption and longwave water vapor greenhouse effects by high clouds play key roles in providing strong positive feedback to the tropospheric warming. In the extratropics, increased atmospheric heat transport associated with changes in the Hadley circulation is balanced by strong longwave cooling above, and warming below due to increased high clouds. We also find a strong positive correlation between daily and pentad heavy rain in the ITCZ core, and expansion of the drier zones coupled to a contraction of the highly convective zones in the ITCZ, indicating a strong tendency RC3I-induced convective aggregation in tropical clouds i.e., wet-regions-get-wetter and contracted, and dry-areas-get-drier and expanded.

Correction to: Sub-cloud moist entropy curvature as a predictor for changes in the seasonal cycle of tropical precipitation - Bryce E. Harrop; Jian Lu; L. Ruby Leung (Climate Dynamics, 2019)

Sub-cloud moist entropy curvature as a predictor for changes in the seasonal cycle of tropical precipitation - Bryce E. Harrop; Jian Lu; L. Ruby Leung (Climate Dynamics, 2019)

South Asian monsoon precipitation in CMIP5: a link between inter-model spread and the representations of tropical convection - Samson Hagos; L. Ruby Leung; Moetasim Ashfaq; Karthik Balaguru (Climate Dynamics, 2019)

Sources of errors in the simulation of south Asian summer monsoon in the CMIP5 GCMs - Moetasim Ashfaq; Deeksha Rastogi; Rui Mei; Danielle Touma; L. Ruby Leung (Climate Dynamics, 2017)

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

Uncertainty and feasibility of dynamical downscaling for modeling tropical cyclones for storm surge simulation - Zhaoqing Yang; Sourav Taraphdar; Taiping Wang; L. Ruby Leung; Molly Grear (Natural Hazards, 2016)

Future hurricane storm surge risk for the U.S. gulf and Florida coasts based on projections of thermodynamic potential intensity - Karthik Balaguru; David R. Judi; L. Ruby Leung (Climatic Change, 2016)

Observed variability of summer precipitation pattern and extreme events in East China associated with variations of the East Asian summer monsoon - Lei Wang; Yun Qian; Yaocun Zhang; Chun Zhao; L. Ruby Leung; Anning Huang; Chuliang Xiao (International Journal of Climatology, 2016)
This article presents a comprehensive analysis of interannual and interdecadal variations of summer precipitation and precipitation‐related extreme events in East China associated with variations of the East Asian summer monsoon ( EASM ) from 1979 to 2012. A high‐quality daily precipitation data set covering 2076 observational stations in China is analysed. Based on the precipitation pattern analysis using empirical orthogonal functions and the regime shift detection method, three sub‐periods of 1979–1992 (period I), 1993–1999 (period II ) and 2000–2012 (period III ) are identified to be representative of the precipitation variability. Similar significant variability of the extreme precipitation indices is found across four sub‐regions in eastern China. The spatial patterns of summer mean precipitation, the number of days with daily rainfall exceeding 95th percentile precipitation (R95p) and the maximum number of consecutive wet days ( CWD ) anomalies are consistent, but opposite to that of maximum consecutive dry days ( CDD ) anomalies to some extent during the three sub‐periods. However, the spatial patterns of hydroclimatic intensity ( HY‐INT ) are notably different from that of the other three extreme indices, but highly correlated to the dry events. The changes of precipitation anomaly patterns are accompanied by the change of the EASM regime and the abrupt shift of the position of the west Pacific subtropical high around 1992/1993 and 1999/2000, respectively, which influence the moisture transport and contributes to the precipitation anomalies. In addition, the EASM intensity is linked to sea surface temperature anomaly over the tropical Indian and Pacific Ocean through its effects on convective activity over the west Pacific that induces the cyclonic or anticyclonic anomaly over the South China and northwest Pacific.

Attributing runoff changes to climate variability and human activities: uncertainty analysis using four monthly water balance models - Shuai Li; Lihua Xiong; Hong-Yi Li; L. Ruby Leung; Yonas Demissie (Stochastic Environmental Research and Risk Assessment, 2016)

The de-correlation of westerly winds and westerly-wind stress over the Southern Ocean during the Last Glacial Maximum - Wei Liu; Jian Lu; L. Ruby Leung; Shang-Ping Xie; Zhengyu Liu; Jiang Zhu (Climate Dynamics, 2015)

Projected changes in mean and interannual variability of surface water over continental China - GuoYong Leng; QiuHong Tang; MaoYi Huang; Yang Hong; Leung L. Ruby (Science China Earth Sciences, 2015)

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

Modeling high-impact weather and climate: lessons from a tropical cyclone perspective - James M. Done; Greg J. Holland; Cindy L. Bruyère; L. Ruby Leung; Asuka Suzuki-Parker (Climatic Change, 2015)

Assessment of uncertainties in the response of the African monsoon precipitation to land use change simulated by a regional model - Samson Hagos; L. Ruby Leung; Yongkang Xue; Aaron Boone; Fernando de Sales; Naresh Neupane; Maoyi Huang; Jin-Ho Yoon (Climate Dynamics, 2014)

Eddy fluxes and sensitivity of the water cycle to spatial resolution in idealized regional aquaplanet model simulations - Samson Hagos; L. Ruby Leung; William I. Gustafson; Balwinder Singh (Climate Dynamics, 2014)

ENSO anomalies over the Western United States: present and future patterns in regional climate simulations - Yongxin Zhang; Yun Qian; Valérie Dulière; Eric P. Salathé; L. Ruby Leung (Climatic Change, 2012)

Simulations of precipitation using NRCM and comparisons with satellite observations and CAM: annual cycle - Aditya Murthi; Kenneth P. Bowman; L. Ruby Leung (Climate Dynamics, 2011)

Role of the atmospheric mean state on the initiation of the Madden-Julian oscillation in a tropical channel model - Pallav Ray; Chidong Zhang; Mitchell W. Moncrieff; Jim Dudhia; Julie M. Caron; L. Ruby Leung; Cindy Bruyere (Climate Dynamics, 2011)

Climate–soil–vegetation control on groundwater table dynamics and its feedbacks in a climate model - L. Ruby Leung; Maoyi Huang; Yun Qian; Xu Liang (Climate Dynamics, 2011)

Regional climate model projections for the State of Washington - Eric P. Salathé; L. Ruby Leung; Yun Qian; Yongxin Zhang (Climatic Change, 2010)

Downscaling hydroclimatic changes over the Western US based on CAM subgrid scheme and WRF regional climate simulations - Yun Qian; Steven J. Ghan; L. Ruby Leung (International Journal of Climatology, 2010)
This study examines two dynamical downscaling methods, a subgrid parameterization and a regional climate model, to compare their impacts on simulating orographic precipitation and surface hydrology in mountain regions. A global climate model was first applied at 1° × 1.25° grid resolution with a subgrid orographic precipitation scheme. The global simulations were then used to drive a regional climate model at 15‐km grid resolution over the Western United States. By comparing the global and regional simulations for two 10‐year periods, 1993–2003 and 2039–2049, this study assesses the two downscaling methods in the context of simulating both the present climate and climate change signals, and the implications of the relatively short simulation length to investigate differences in current and future climate simulated by the models are discussed. The model results show that improving the representation of surface topography through higher spatial resolution or a subgrid method has a large impact on the simulations. Both the subgrid scheme and the regional model significantly improved the simulation of snowpack in the mountains. The spatial distributions of precipitation and snowpack are generally consistent between the subgrid and regional simulations, since they were driven by the same large‐scale circulation from the global simulations. However, because rain‐shadow effects are not represented in the subgrid scheme, the regional simulations produced much more realistic spatial variability in precipitation and snowpack than the subgrid simulations in narrow mountain ranges. In the climate change experiments, both downscaling procedures preserved the large‐scale patterns of temperature and precipitation changes in the global simulations. However, the regional simulations show larger changes in precipitation and snowpack along the coastal mountains than the subgrid simulations. This is attributed to the fact that the regional model explicitly simulates the interactions of atmospheric circulation and the underlying topography, so changes in wind directions with respect to the orientations of the mountains may lead to changes in orographic precipitation that cannot be explained by changes in atmospheric temperature and moisture alone. Hence differences between the precipitation changes simulated by the regional model and the subgrid method are larger in narrow mountains such as the Cascades and the Sierra Nevada because the subgrid method does not account for the influence of mountain orientations at the subgrid scale. As precipitation is an important driver of surface hydrological processes, differences between the precipitation changes simulated by the two methods lead to important differences in the surface hydrological processes under climate change. Copyright © 2009 Royal Meteorological Society

Predicting future threats to the long-term survival of Gila trout using a high-resolution simulation of climate change - Thomas L. Kennedy; David S. Gutzler; Ruby L. Leung (Climatic Change, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Mid-Century Ensemble Regional Climate Change Scenarios for the Western United States - L. Ruby Leung; Yun Qian; Xindi Bian; Warren M. Washington; Jongil Han; John O. Roads (Climatic Change, 2004)

Elevation Dependence of Winter Wheat Production in Eastern Washington State with Climate Change: A Methodological Study - Allison M. Thomson; Robert A. Brown; Steven J. Ghan; R. Cesar Izaurralde; Norman J. Rosenberg; L. Ruby Leung (Climatic Change, 2002)